La utilización del vídeo para la enseñanza de conceptos básicos (calor y temperatura) - Insausti, M. J.; Beltrán, M. T.; Crespo, M. S.; García, R. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
The goal of one of the inquiries implemented in the ANTEC Project (Aplicación de las Nuevas Tecnologías a la Enseñanza de las Ciencias) was to analyze the use of videotapes as a means to teach Sciences. In this paper we present the use of vídeotapes related to Heat and Temperature Units, in classrooms with students who were 16 years old. We expected to modify their concepts about these subjects. The results suggest the improvement of students' concepts and vocabulary, although it was not the same with the application of scientific knowledge to everyday events.